2002
DOI: 10.1124/jpet.301.3.953
|View full text |Cite
|
Sign up to set email alerts
|

Pardaxin Stimulation of Phospholipases A2and Their Involvement in Exocytosis in PC-12 Cells

Abstract: Pardaxin (PX) is a voltage-dependent ionophore that stimulates catecholamine exocytosis from PC-12 pheochromocytoma cells both in the presence and absence of extracellular calcium. Using a battery of phospholipase A(2) inhibitors we show that PX stimulation of phospholipase A(2) (PLA(2)) enzymes is coupled with induction of exocytosis. We investigated the relationship between PX-induced PLA(2) activity and neurotransmitter release by measuring the levels of arachidonic acid (AA), prostaglandin E(2) (PGE(2)), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The observation that arachidonic acid had a stimulatory effect on exocytosis is also consistent with the results of previous studies, which showed increase in exocytosis in PC12 cells after PLA 2 activation (28,29). In addition, cPLA 2 alphaevoked formation of arachidonic acid and lysophospholipids was found to be required for exocytosis in mouse pancreatic beta-cells (30).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observation that arachidonic acid had a stimulatory effect on exocytosis is also consistent with the results of previous studies, which showed increase in exocytosis in PC12 cells after PLA 2 activation (28,29). In addition, cPLA 2 alphaevoked formation of arachidonic acid and lysophospholipids was found to be required for exocytosis in mouse pancreatic beta-cells (30).…”
Section: Discussionsupporting
confidence: 92%
“…In this context, it is possible that eicosapentaenoic acid and arachidonic acid could present the ideal combination of acyl length/unsaturation necessary for optimal fluidity of the cell membrane and vesicle fusion. It has been reported that the fusion of synaptic vesicles with presynaptic membrane induced by arachidonic acid or PLA 2 activity could occur independently of calcium ions (33) or a key protein of the SNARE complex, SNAP-25 (29).…”
Section: Discussionmentioning
confidence: 99%
“…Paradaxin, a voltage-dependent ionophore that releases catecholamine from PC-12 pheochromocytoma cells, was revealed to activate iPLA 2 to stimulate AA release and eicosanoid production, which facilitate catecholamine release through an increase in fusion of vesicle to membranes. 38) In rat mesenteric resistance arteries, acetylcholinemediated vascular relaxation was attenuated by BEL, and external addition of AA to BEL-treated cells restored the relaxation completely. 39) These results suggest that AA released by iPLA 2 plays an important role in acetylcholine-induced relaxation in the arteries.…”
Section: Involvement In Cellular Signalingmentioning
confidence: 99%
“…Arachidonic acid and its metabolites are likely candidates in Ca 2+ -independent neurotransmitter release [17,34]. PLA 2 s are involved in a variety of cellular functions, including signal transduction and exocytosis [19,35].…”
Section: Discussionmentioning
confidence: 99%
“…PLA 2 s are involved in a variety of cellular functions, including signal transduction and exocytosis [19,35]. In a number of studies with PC12 cells, PLA 2 s are suggested to be involved in both Ca 2+ -dependent exocytosis [36,37,38,39] and in Ca 2+ -independent [34] exocytosis. All major PLA 2 groups (cPLA 2 s, sPLA 2 s, and Ca 2+ -independent iPLA 2 s) are present in the central nervous system [40,41], and iPLA 2 was also suggested to be the major PLA 2 in the cytosolic fraction of developing and adult rat brains [42].…”
Section: Discussionmentioning
confidence: 99%